Animation Film Design As a Promotional Media for Spiritual Tourism of Batur Traditional Village - Janottama, I Putu Arya; Indira, Wahyu; Putra, Gede Bayu Segara (Sean Institute, 2024)
Batur Village is located in the Kintamani hilly area of ​​Bangli Regency. The history of Batur Village is influenced by the frequent eruptions of ancient Batur. It is estimated that the first eruption of ancient Mount Batur occurred 29,300 years ago, starting with the spewing of volcanic material as far as 84 kilometers, forming the first caldera. A series of eruptions occurred which resulted in beautiful cliffs along the road between Besakih and Penelokan. Its beauty attracts domestic and foreign tourists, but not many people know that Batur Village has spiritual tourism among its many potentials. With the emergence of the trend of religious tourism on the island of Bali, the fact that Batur Village has many holy places makes it have a very big opportunity. Through this research, the author created an animation in an effort to promote Batur Village as a Spiritual Tourism Destination. The creation method used in designing visual communication media for the Promotion of Batur Village as a Spiritual Tourism Destination with the Tri Hita Karana Concept is the design thinking method which is divided into three stages, namely inspiration, conception (ideation) and realization (implementation).